POTENSI DAYA TARIK WISATA TAMAN NASIONAL BROMO TENGGER SEMERU (ANALISIS SWOT OBJEK WISATA BROMO PINTU CEMORO LAWANG, PROBOLINGGO) - Achmad Zurohman; Kurnia Maulidi Noviantoro; Khofifaturrohmah; Sundus Nuril Firdausi (Al-Fikru : Jurnal Pendidikan Dan Sains, 2021)
The purpose of this study is to describe and identify potentials that are not optimal in the development of the Bromo Tengger Semeru National Park tourist area on the Cemoro Lawang route, Probolinggo Regency. This study uses a descriptive qualitative approach through the methods of observation, interviews, and documentation. The data analysis technique is through stages; data reduction, data modeling, data classification and interpretation of the results of data analysis or drawing conclusions. The data sources in this study were selected purposively, namely based on certain reasons or considerations and were snowball sampling. The research findings explain that the potential for tourist attractions in the Bromo-Tengger area with a SWOT analysis is quite good. The potential for tourist attraction in the Bromo-Tengger area is supported by the complexity of supporting elements that are very synergistic, so that it can become a beautiful tourist attraction, both elements in the Bromo-Tengger area itself such as natural resources, the culture of the surrounding community and their beliefs as well as the attention of the local government to each other. support the development of Mount Bromo tourism object so that it becomes famous. Local government policies in the development of Mount Bromo are manifested in increasing the establishment of infrastructure to support the smooth flow of tourists visiting BromoTengger tourism objects.Key Word: Potential, Tourist Attraction, SWOT.